Analysis of the Unified Theory of Acceptance and Use of Technology 3 (Utaut 3) Model on Users’ Intention to Use the Linkaja Application in Malang City - Elvis Berty, Edwardus Bernard; Wicaksono , Aries (CV. Publikasi Indonesia, 2025)
The purpose of this study is to apply the Unified Theory of Acceptance and Use of Technology 3 (UTAUT 3) model to examine user interest in the LinkAja application in Malang City. Twelve factors of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and personal innovation in IT were identified in this study as factors influencing user interest. The statistical method used was descriptive statistics using the SmartPLS 4 tool. Researchers found 140 respondents in Malang City who responded to the distributed questionnaire. The findings showed that behavioral intention was not significantly influenced by factors such as performance expectancy, effort expectancy, social influence, facilitating conditions, price value, or personal innovation in IT. In addition, application usage behavior was significantly influenced by personal innovation in IT, indicating that more creative people were more likely to use the application. This study provides suggestions to LinkAja application developers on how to improve the application's functionality and usability while increasing the social impact on community acceptance.